(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2022)
Chronic liver disease is a uncommon manifestation in the children and many of them presents with oesophageal varices. The aim of this study was to observe the association between severity of chronic liver diseases determined by Child- Pugh score with grading of oesophageal varices. 62 cases (male, 34) were included in the present study. Mean age of the study population was 9.5±3.3 years. Male to female ratio was 1.2:1. Wilson’s disease was the most common etiology of chronic liver disease (64.5%). Of the 62 children, 30.7% had Child class A, 16.1% had Child class B and the remaining 53.2% had Child class C cirrhosis. Oesophageal varices were found in 43 (69.3%) children. On univariate ananlysis low platelet count and splenomegaly were found to be associated with the presence of esophageal varices. Splenomegaly was found as independent predictor for presence of varices on multivariate analysis (OR; 15.51, 95% CI, 3.7-63.5). Furthermore, splenomegaly was also independent risk factor for large esophageal varices. No association was found between Child-Pugh classification (child A, B, C) with grading of oesophageal varices (Grade - I, II, III, IV). Our study showed no positive association between Child-Pugh classifications with grading of esophageal varices. Splenomegaly predicts the presence of oesophageal varices as well as the presence of large esophageal varices. BSMMU J 2022; 15(1): 29-34